Soybean Seed Enrichment with Cobalt and Molybdenum as an Alternative to Conventional Seed Treatment - Abreu-Junior, Cassio Hamilton; Gruberger, Gabriel Asa Corrêa; Cardoso, Paulo Henrique Silveira; Gonçalves, Paula Wellen Barbosa [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Capra, Gian Franco; Jani, Arun Dilipkumar (MDPI, 2023)
Biological nitrogen fixation in soybean is enhanced when seed is treated with cobalt (Co) and molybdenum (Mo) prior to planting. In this study, our objective was to verify if Co and Mo application during the reproductive phase of the crop increases seed Co and Mo concentration without adverse effects on seed quality. Two experiments were conducted. First, we investigated foliar and soil Co and Mo application under greenhouse conditions. Next, we validated the results obtained in the first study. The treatments for both experiments consisted of Co doses combined with Mo, and a control without Co and Mo application. The foliar application was more efficient in producing enriched Co and Mo seed; meanwhile, as Co doses increased so did Co and Mo concentrations in the seed. There were no adverse effects on nutrition, development, quality, and yield of parent plants and seed when these micronutrients were applied. The seed showed higher germination, vigor, and uniformity for the development of soybean seedlings. We concluded that the application of 20 g ha−1 Co and 800 g ha−1 Mo via foliar application at the reproductive stage of soybean increased germination rate and achieved the best growth and vigor index of enriched seed.
Keywords: Cerrado; germination; Glycine max; plant nutrition; seed quality